Composite ferrocenyl modified nano wave-absorbing agent as well as preparation method and application thereof
By modifying multi-walled carbon nanotubes, graphene oxide, and nanocarbon black ferrocene and forming a composite absorbing network, the problem of poor dispersion of carbon materials in composite absorbing materials is solved, and the absorption performance is significantly improved and Electromagnetic shielding efficiency.
Patent Information
- Application Number
- CN202411169145.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2024-12-17
AI Technical Summary
Existing carbon materials such as graphene, nanocarbon tubes, and nanocarbon black are difficult to disperse evenly in composite wave absorbing materials, affecting the wave absorbing performance, especially poor compatibility with resin matrix, which leads to difficulty in building a wave absorbing network.
By surface modification of ferrocene derivatives on multi-walled carbon nanotubes, graphene oxide, and nanocarbon black, ferrocene-based modified nanowave absorbers are formed, and the shapes of linear, sheet-like, and granular materials are passed through the shapes of Complementary to form a composite wave absorption network.
The dispersion of the wave absorber in the organic solvent and the electromagnetic shielding efficiency are significantly improved, and a high-performance composite wave absorbing material is formed, which improves the absorption capacity of the electromagnetic wave.
Smart Images

Figure CN119155974A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional materials, and in particular relates to a composite ferrocene-based modified nanometer wave absorbing agent, a preparation method and an application thereof. Background Art
[0002] With the advancement of science and technology, electromagnetic waves have been widely used in wireless communications, medical care, military industry, etc., but the radiation generated by electromagnetic waves also brings a series of problems, which will endanger people's health and affect the normal operation of surrounding electronic equipment, especially in the fields of national defense and aviation, which will interfere with or detect important equipment. In order to overcome the adverse effects of electromagnetic waves, it is very urgent to develop high-performance absorbing materials.
[0003] Carbon materials such as graphene, carbon nanotubes, and nano carbon black have excellent dielectric properties, good composite properties, special microstructures, light weight, and strong chemical stability, and have good application prospects in the field of wave absorption. Studies have shown that graphene, carbon nanotubes, etc. not only have a high electrical loss tangent angle, but can absorb electromagnetic waves by relying on the electronic polarization or interface polarization attenuation of the medium. In addition, due to the quantum confinement effect, the movement of electrons inside them is axial. Due to the relationship between electron energy and wave vectors, they exhibit metal or semiconductor characteristics and have excellent wave absorption properties. When carbon materials are applied to composite wave absorbing materials, the construction of the wave absorbing network and the dispersion of the wave absorbing components in the resin matrix have an important influence on the wave absorbing properties of the resulting composite material. However, carbon materials such as graphene, carbon nanotubes, and nano carbon black have surface inertness and poor compatibility with the matrix resin, making them difficult to disperse evenly. Summary of the invention
[0004] The first object of the present invention is to provide a composite ferrocene-modified nano absorber.
[0005] To this end, the above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0006] The composite ferrocene-modified nano absorber is prepared by surface-modifying multi-walled carbon nanotubes, graphene oxide and nano carbon black with ferrocene derivatives to obtain three ferrocene-modified nano absorbers, and then at least two ferrocene-modified nano absorbers are compounded to form a composite absorbent network through shape complementarity between linear ferrocene-modified multi-walled carbon nanotubes, flaky ferrocene-modified graphene oxide and granular ferrocene-modified carbon black.
[0007] While adopting the above technical solutions, the present invention may also adopt or combine the following technical solutions:
[0008] As a preferred technical solution of the present invention: the ferrocene derivative is ferrocenecarboxylic acid.
[0009] As a preferred technical solution of the present invention: the multi-walled carbon nanotubes are surface-modified by hydroxylation, and the hydroxyl content is 0.3-0.6 mmol / g.
[0010] As a preferred technical solution of the present invention: the graphene oxide is surface-hydroxylated and the hydroxyl content is 0.3-0.6 mmol / g.
[0011] As a preferred technical solution of the present invention: the nano carbon black is surface-hydroxylated and has a hydroxyl content of 0.3 to 0.6 mmol / g.
[0012] As a preferred technical solution of the present invention: the preparation method of the ferrocene-modified nano absorber comprises the following steps:
[0013] S1. Add ferrocenecarboxylic acid, dichloromethane and pyridine into a reaction vessel and stir until completely dissolved, then slowly add oxalyl chloride, react at 20°C to 25°C for 0.5 hour, then heat to reflux dichloromethane for 5 hours, remove the solvent in vacuo, then add petroleum ether with a boiling range of 60 to 90°C and reflux for 2 hours, filter while hot to obtain a filtrate, remove the solvent in vacuo, and dry to obtain ferrocenecarboxylic acid chloride;
[0014] S2. Add the obtained ferrocenecarbonyl chloride, surface hydroxylated modified nano carbon black or multi-walled carbon nanotube or graphene oxide, dichloromethane and triethylamine into a reaction container, stir to react, filter and wash after the reaction, and dry to obtain ferrocene-modified nano carbon black or ferrocene-modified multi-walled carbon nanotube or ferrocene-modified graphene oxide.
[0015] As a preferred technical solution of the present invention: in step S1, the mass ratio of ferrocenecarboxylic acid to surface hydroxylated modified nano carbon black or multi-walled carbon nanotube or graphene oxide is 2 to 10:1.
[0016] As a preferred technical solution of the present invention, three or two ferrocene-modified nano absorbers, namely, ferrocene-modified nano carbon black, ferrocene-modified multi-walled carbon nanotubes and ferrocene-modified graphene oxide, are compounded by ball milling.
[0017] As a preferred technical solution of the present invention: the ball milling time is 2 to 10 hours, and the rotation speed is 100 to 500 rpm.
[0018] Another object of the present invention is to provide application of ferrocene-based composite nanomaterials in electromagnetic wave absorption.
[0019] To this end, the above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0020] The invention discloses an application of ferrocene-based composite nanomaterials in electromagnetic wave absorption. The ferrocene-based composite nanomaterials are prepared by surface-modifying multi-walled carbon nanotubes, graphene oxide, and nano carbon black with ferrocene derivatives respectively to obtain three ferrocene-based modified nano absorbers, and then compounding at least two ferrocene-based modified nano absorbers to form a ferrocene-based composite nanomaterial with a composite wave absorption network through shape complementarity between linear ferrocene-based modified multi-walled carbon nanotubes, flaky ferrocene-based modified graphene oxide, and granular ferrocene-based modified carbon black.
[0021] The present invention provides a composite ferrocene-modified nano absorber, a preparation method and an application thereof. Multi-walled carbon nanotubes, graphene oxide and nano carbon black are respectively surface-modified with ferrocene derivatives to obtain three ferrocene-modified nano absorbers, and then at least two ferrocene-modified nano absorbers are compounded. Through the shape complementarity between linear ferrocene-modified multi-walled carbon nanotubes, flaky ferrocene-modified graphene oxide and granular ferrocene-modified carbon black, a composite absorber network is formed, which has good absorber performance. When the composite absorber is used to prepare an absorber coating, the ferrocene group modified on the surface of the absorber can increase its dispersibility in an organic solvent and promote the dispersion effect. The present invention forms a better absorber network by ferrocene-modifying carbon materials of different shapes and then complementing their shapes during the compounding process, which has good absorber performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 These are the infrared spectra of ferrocene-modified nano-carbon black, ferrocene-modified multi-walled carbon nanotubes, and ferrocene-modified graphene oxide.
[0023] Figure 2 After being modified with ferrocene, its dispersibility in ethanol is significantly improved.
[0024] Figure 3 The microwave absorption performance curve diagram of ferrocene-modified nano carbon black (1), ferrocene-modified multi-walled carbon nanotube (2), ferrocene-modified graphene oxide (3) and composite ferrocene-modified nano microwave absorber (4) is shown. DETAILED DESCRIPTION
[0025] The present invention will be described in further detail with reference to the accompanying drawings and specific embodiments.
[0026] Example 1
[0027] 8 g of dry ferrocenecarboxylic acid was added into a round-bottom flask, followed by 100 ml of dried dichloromethane and 6 ml of pyridine. Under argon protection, 7 ml of oxalyl chloride was slowly added dropwise. After reacting at room temperature for 0.5 hour, the reaction oil bath temperature was raised to 50°C for 8 hours. The liquid component was removed by vacuuming. 100 ml of petroleum ether with a boiling range of 60-90°C was added, and the oil bath temperature was refluxed at 90°C for 2 hours. The mixture was filtered through a sand core funnel while hot, and the petroleum ether was removed by vacuuming the filtrate to obtain ferrocenecarboxylic acid chloride.
[0028] 1 gram of surface hydroxylated modified nano carbon black, 4 grams of ferrocene carbonyl chloride, and 30 milliliters of dichloromethane were added to a three-necked flask, argon was passed through, ultrasonic dispersion was performed for 15 minutes, and then heated to 50°C in an oil bath, and stirred for 16 hours. After the reaction was completed, dichloromethane was removed by filtration under reduced pressure, and then washed with THF (tetrahydrofuran) 3 to 4 times, washed with a large amount of deionized water 3 to 4 times, and dried in a vacuum drying oven at 50°C to constant weight to obtain ferrocene-modified nano carbon black.
[0029] The infrared spectrum of ferrocene-modified nano carbon black is as follows Figure 1 As shown, at 1100cm -1 , 1000cm -1 、820cm -1 The characteristic absorption peak of ferrocene appears at , indicating that ferrocene is attached to the nano-carbon black.
[0030] The dispersion effect of ferrocene-modified nanocarbon black in organic solvents is tested as follows: Figure 2 As shown, compared with nano carbon black, the dispersibility of ferrocene-modified nano carbon black in ethanol is significantly improved.
[0031] Example 2
[0032] 11 g of dry ferrocenecarboxylic acid was added into a round-bottom flask, followed by 150 ml of dried dichloromethane and 9 ml of pyridine. Under argon protection, 10 ml of oxalyl chloride was slowly added dropwise. After reacting at room temperature for 0.5 hour, the reaction oil bath temperature was raised to 50°C for 8 hours. The liquid component was removed by vacuuming. 150 ml of petroleum ether with a boiling range of 60-90°C was added, and the oil bath temperature was 90°C for 2 hours. The mixture was filtered through a sand core funnel while hot, and the petroleum ether was removed by vacuuming the filtrate to obtain ferrocenecarboxylic acid chloride.
[0033] 1 gram of surface hydroxylated multi-walled carbon nanotubes, 6 grams of ferrocenecarbonyl chloride, and 30 milliliters of dichloromethane were added to a three-necked flask, argon was passed through, ultrasonic dispersion was performed for 15 minutes, and then heated to 50°C in an oil bath, and stirred for 16 hours. After the reaction was completed, dichloromethane was removed by filtration under reduced pressure, and then washed with THF (tetrahydrofuran) for 3 to 4 times, washed with a large amount of deionized water for 3 to 4 times, and dried in a vacuum drying oven at 50°C to constant weight to obtain ferrocene-modified multi-walled carbon nanotubes.
[0034] The infrared spectrum of ferrocene-modified multi-walled carbon nanotubes is shown in Figure 1 As shown, at 1120cm -1 、1050cm -1 、818cm -1 The characteristic absorption peak of ferrocene appears at , indicating that ferrocene is attached to the multi-walled carbon nanotubes.
[0035] The dispersion effect of ferrocene-modified multi-walled carbon nanotubes in organic solvents was tested. Figure 2 As shown, compared with multi-walled carbon nanotubes, the dispersibility of ferrocene-modified multi-walled carbon nanotubes in ethanol is significantly improved.
[0036] Example 3
[0037] 15 g of dry ferrocenecarboxylic acid was added into a round-bottom flask, followed by 150 ml of dried dichloromethane and 9 ml of pyridine. Under argon protection, 15 ml of oxalyl chloride was slowly added dropwise. After reacting at room temperature for 0.5 hour, the reaction oil bath temperature was raised to 50°C for 8 hours. The liquid component was removed by vacuuming. 150 ml of petroleum ether with a boiling range of 60-90°C was added, and the oil bath temperature was 90°C for 2 hours. The mixture was filtered through a sand core funnel while hot, and the petroleum ether was removed by vacuuming the filtrate to obtain ferrocenecarboxylic acid chloride.
[0038] 1 gram of surface hydroxylated graphene oxide, 8 grams of ferrocenecarbonyl chloride, and 30 milliliters of dichloromethane were added to a three-necked flask, argon was passed through, ultrasonic dispersion was performed for 15 minutes, and then heated to 50°C in an oil bath, and stirred for 16 hours. After the reaction was completed, dichloromethane was removed by filtration under reduced pressure, and then washed with THF (tetrahydrofuran) 3 to 4 times, washed with a large amount of deionized water 3 to 4 times, and dried in a vacuum drying oven at 50°C to constant weight to obtain ferrocene-modified graphene oxide.
[0039] The infrared spectrum of ferrocenyl-modified graphene oxide is shown in Figure 1 As shown, 1452cm -1 、1133cm -1 and 814cm -1 The characteristic absorption peak of ferrocene appears at , indicating that ferrocene is attached to graphene oxide.
[0040] The dispersion effect of ferrocene-modified graphene oxide in organic solvents was tested as follows: Figure 2 As shown, compared with graphene oxide, the dispersibility of ferrocene-modified graphene oxide in ethanol is significantly improved.
[0041] Example 4
[0042] 0.2 g each of ferrocene-modified nano carbon black, ferrocene-modified multi-walled carbon nanotubes and ferrocene-modified graphene oxide were added into the tank of a ball mill and ball-milled at 300 rpm for 6 hours to obtain a composite ferrocene-modified nano absorber.
[0043] The wave absorption performance test curves of the composite ferrocene-modified nano absorber, ferrocene-modified nano carbon black, ferrocene-modified multi-walled carbon nanotubes, and ferrocene-modified graphene oxide are shown in the figure. Figure 3 As shown, specifically, the sample preparation process is as follows: 40wt% of ferrocene-modified nano carbon black, ferrocene-modified multi-walled carbon nanotubes, and ferrocene-modified graphene oxide are added to solid paraffin respectively, the ratio of the three in the composite ferrocene-modified nano absorber is 1:1:1, and the content in the solid paraffin is 40wt%.
[0044] like Figure 3 As shown, within the test frequency range, the maximum electromagnetic shielding efficiency of ferrocene-modified nano-carbon black is about 11dB, the maximum electromagnetic shielding efficiency of ferrocene-modified multi-walled carbon nanotubes is about 19dB, the maximum electromagnetic shielding efficiency of ferrocene-modified graphene oxide is about 22dB, and the maximum electromagnetic shielding efficiency of the composite ferrocene-modified nano-absorbent is about 25dB, indicating that the absorbing performance of the composite ferrocene-modified nano-absorbent is far superior to the other three types of ferrocene-modified nano-carbon black, ferrocene-modified multi-walled carbon nanotubes, and ferrocene-modified graphene oxide tested separately.
[0045] The above-mentioned specific implementation methods are used to explain the present invention and are only preferred embodiments of the present invention, rather than limiting the present invention. Any modifications, equivalent substitutions, improvements, etc. made to the present invention within the spirit of the present invention and the protection scope of the claims shall fall within the protection scope of the present invention.
Claims
1. A composite ferrocene-modified nano absorber, characterized in that: Multi-walled carbon nanotubes, graphene oxide, and nano carbon black are respectively surface-modified with ferrocene derivatives to obtain three ferrocene-modified nano absorbers, and then at least two ferrocene-modified nano absorbers are compounded to form a composite absorbing network through shape complementarity between linear ferrocene-modified multi-walled carbon nanotubes, flaky ferrocene-modified graphene oxide, and granular ferrocene-modified carbon black.
2. The composite ferrocene-modified nano absorber according to claim 1, characterized in that: The ferrocene derivative is ferrocenecarboxylic acid.
3. The composite ferrocene-modified nano absorber according to claim 1, characterized in that: The multi-walled carbon nanotubes are surface-modified by hydroxylation.
4. The composite ferrocene-modified nano absorber according to claim 1, characterized in that: The graphene oxide is surface-modified by hydroxylation.
5. The composite ferrocene-modified nano absorber according to claim 1, characterized in that: The nano carbon black is surface-modified by hydroxylation.
6. The composite ferrocene-modified nano absorber according to claim 1, characterized in that: The preparation method of the ferrocene-modified nano absorber comprises the following steps: S1. Add ferrocenecarboxylic acid, dichloromethane and pyridine into a reaction vessel and stir until completely dissolved, then slowly add oxalyl chloride, react at 20°C to 25°C for 0.5 hour, then heat to reflux dichloromethane for 5 hours, remove the solvent in vacuo, then add petroleum ether with a boiling range of 60 to 90°C and reflux for 2 hours, filter while hot to obtain a filtrate, remove the solvent in vacuo, and dry to obtain ferrocenecarboxylic acid chloride; S2. Add the obtained ferrocenecarbonyl chloride, surface hydroxylated modified nano carbon black or multi-walled carbon nanotube or graphene oxide, dichloromethane and triethylamine into a reaction container, stir to react, filter and wash after the reaction, and dry to obtain ferrocene-modified nano carbon black or ferrocene-modified multi-walled carbon nanotube or ferrocene-modified graphene oxide.
7. The composite ferrocene-modified nano absorber according to claim 6, characterized in that: In step S1, the mass ratio of ferrocenecarboxylic acid to surface hydroxylated modified nano carbon black or multi-walled carbon nanotube or graphene oxide is 2 to 10:
1.
8. The composite ferrocene-modified nano absorber according to claim 1, characterized in that: The three or two ferrocene-modified nano absorbers, namely ferrocene-modified nano carbon black, ferrocene-modified multi-walled carbon nanotubes and ferrocene-modified graphene oxide, are compounded by ball milling.
9. The composite ferrocene-modified nano absorber according to claim 8, characterized in that: The ball milling time is 2 to 10 hours, and the rotation speed is 100 to 500 rpm.
10. Application of ferrocene-based composite nanomaterials in electromagnetic wave absorption, characterized by: The ferrocene-based composite nanomaterial is prepared by surface-modifying multi-walled carbon nanotubes, graphene oxide, and nano carbon black with ferrocene derivatives respectively to obtain three ferrocene-based modified nano absorbers, and then compounding at least two ferrocene-based modified nano absorbers. The ferrocene-based composite nanomaterial with a composite absorbing network is formed by shape complementarity between linear ferrocene-modified multi-walled carbon nanotubes, flaky ferrocene-modified graphene oxide, and granular ferrocene-modified carbon black.
